Profil Ergonomis dan Proporsi Keluhan Muskuloskeletal pada Tenaga Kerja Bongkar Muat di Pelabuhan Bongkar Muat Kota Pekanbaru - Laode Burhanuddin M; Suyanto Suyanto; Zulfikar Zulfikar (Fakultas Kedokteran Universitas Riau, 2017)
Ergonomics deals with optimization, efficiency, health, safety, and comfort in the workplace. One ofthis ergonomics principle approach is important for unloading workers in the harbour, because theirworkplace and work-system have high risk of workplace accidents if the principles of ergonomics isnot applied. So, the effectivity, efficiency, productivity, comfort, and health of workers in the harbourneed to be maintained and improved with ergonomics approach. This research was held on harbourin Pekanbaru city , with descriptive observasional method to describe risk of work ergonomy causedby bad application of ergonomics at work and musculosceletal symptoms proportion of 19 unloadingworkers by Nordic Body Map (NBM) questionnaire. The result is all unloading workers (100%) havemusculosceletal injury with various grade of injury. When being observed, none of all unloadingworkers lift the load with the right method and no special technique had been used by unloadingworkers to lift the load.